A FOURTEEN-YEAR-OLD GIRL WITH HAEMORRHAGIC FEVER WITH RENAL SYNDROME - Špela Urankar Brvar; Maja Arnež; Simona Bizjak Vojinovič (Slovenska pediatrija, 2022)

(untitled)
In 2021, Slovenia faced an outbreak of hantavirus infection, which causes haemorrhagic fever with renal syndrome. In children, haemorrhagic fever with renal syndrome is rare. In this article, we present a 14-year-old girl with haemorrhagic fever with renal syndrome, which was caused by Puumala virus.